Temporal variation of chronic child malnutrition in the context of strengthening healthcare services in Burkina Faso: an Oaxaca-Blinder multivariate decomposition analysis - Sawadogo, Pengdewendé Maurice; Kobiané, Jean-François; Tchouaket Nguemeleu, Eric (Frontiers in Public Health, 2024)
Malnutrition seriously affects children's health, survival, and future productivity. According to the literature, increasing the supply of health services should help reduce the spread of malnutrition. This article analyses the sources of changes in the decline of chronic malnutrition during the 2000s, where there was an increase in the supply of health services in Burkina Faso.We used data from demographic and health surveys conducted in 2003 and 2010 in Burkina Faso. Malnutrition was defined according to the recommendations of the World Health Organization, while using standards of growth which are current and uniform for the two periods of study considered. We analyzed the source of temporal variation of chronic malnutrition through the Oaxaca-Blinder multivariate decomposition of the proportion of children suffering from chronic malnutrition.The analyses showed that the relative extent of chronic malnutrition in children decreased significantly, from 43.4% ) in 2003 to 34.7% (CI 95%:33.6-35.9) in 2010. A quarter of this variation is due to a change in characteristics (composition effect), and the remaining 74.74% is due to a difference in coefficients (performance or behavior effect). Improved access to health services played a crucial role in reducing the scale of chronic malnutrition between 2003 and 2010. Other factors, such as educating mothers and urbanization, also contributed significantly.This study shows that improving access to health services is crucial for reducing chronic malnutrition. So, programs tackling child malnutrition must first and foremost ensure that children have access to health services.